Pemberdayaan masyarakat Pulau Lae-Lae Kota Makassar - Patang Patang; Andi Heryanti Rukka (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Community empowerment activities on the la-laeisland of Makassar is to train and improve community skills inprocessing fishery products and utilizing household waste tobe used as trinkets. Partner problems are Teenage women orfishermen who do not have a permanent job who every dayonly works to help his parents at home and various otherunproductive activities and fishermen mothers who have thetalent to create new jobs such as the processing of fisheryproducts that are abundant on this island. The solution offeredis training and mentoring related to the manufacture oftrinkets from household waste and abundant fisheryprocessing on lae-Lae Island. Based on the results of thisactivity, then teenage women become skilled in makingtrinkets from household waste and can be judged as a sourceof livelihood or used for their own purposes. Besides that, thefishermen mothers also skilled in processing fishery productswhich can be used for own needs and sold as a source ofincome.